Android-Based Public Service Reporting Application (Case Study Makassar Ombudsman) - Mubarak, Muhammad Fathul (Institute of Computer Science (IOCS), 2023)
The Makassar City Ombudsman currently still relies on the acceptance of reports and monitoring carried out by the community on forms of public services that are still manual. This means that the community in this case must come directly to the ombudsman institution. This shows that effective and efficient public services have not yet been created with the principles of fast, precise and low cost. The design in building this system is use case diagrams, class diagrams, sequence diagrams and flowcharts. The purpose of this study is to design a public service reporting application that performs android-based night-in-administration. The type of research used is a type of qualitative research with the method of Design and creation. This application runs on the Android operating system, designed with the Java programming language. This research uses interview and documentation methods. The application design method used is the waterfall. The system testing technique used in this research is black box testing. Based on the research results, this application can be used to assist and make it easier for the public to report violations of the law and dissatisfaction with public services carried out by state institutions, both by government institutions, including State-Owned Enterprises (BUMN), State-Owned Legal Entities ( BHMN) and Regional Owned Enterprises (BUMD) as providers of public services which in carrying out their duties and functions in accordance with the regulations and laws that apply to the Ombudsman quickly, efficiently and cheaply.